SCHIZOPHRENIA SYMPTOMS ACUTE IN TEDDY ALIAS ANDREW IN THE “SHUTTER ISLAND” NOVEL BY DENNIS LEHANE - Elfi Rahmi; Tomi Arianto (BASIS (Bahasa dan Sastra Inggris), 2019)
This research discussed about schizophrenia symptoms in Teddy alias Andrew Laedis that was acute and dangerous and also discussed the psychodrama treatment for Andrew. The main character is described to have a dangerous illness which is schizophrenia due to get from his traumatic events in world of war. Some of traumatic event that Andrew is experienced actually like when Andrew killed hundred soldier during the war in Dachau, his guilt because he did not bring his wife, Dolores to psychiatrists then unpredictable his wife killed her three children and drowning her child in a pond and regret for the rest of his life who was forced to kill his beloved wife until die and he finally lost all his family. Andrew cannot escape from the reality and without unconsciously he became experiencing mental disorder. The fictional story written by Dennis Lehane (2003.This novel was using the theory of psychoanalysis approach by Sigmund Freud. By using the concept of Sigmund's theory this research examined the symptoms of acute schizophrenia in Teddy alias Andrew's character which showed that his id is more dominant than his ego and the superego did not almost non-existent. Andrew points out three types of self defense mechanisms, namely, denial projections, regression and displacement. Meanwhile, the process of psychiatric recovery treatment by Dr. Cawley is used a psychodrama.